Minimum trends in air temperature in the municipality of Porto Velho - RO from 1971 to 2016 - Ruezzene, Camila Bermond; Aguiar, Renata Gonçalves; Fischer, Graciela Redies; Andrade, Nara Luísa Reis de; Miranda, Renato Billia de; Mauad, Frederico Fabio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
In recent years, studies focused on the climate of the Amazon have been the focus of major research mainly to identify possible temperature trends. The objective of this study was to analyze the trends and the years of abrupt changes in temperature that occurred in the Southwest Amazon from 1971 to 2016 in the municipality of Porto Velho-RO. The study area is located in the municipality of Porto Velho at the Meteorological Station of Surface, we used average daily temperature data and subdivided into climatological series from 1971 to 2006 and 1981 to 2016. The Mann-Kendall and Pettitt tests were used to verify trends. A positive trend was observed for the Mann-Kendall test for the months of January, February, March, April, June, September, October and December of 1971 to 2006 and for the years 1981 to 2016 only the months of March and June presented a trend temperature increase. The Pettitt test indicated a sudden change in the data series coinciding with most of the months that showed a tendency to increase the minimum air temperature by the Mann-Kendall test in the years 1971 to 2006. From 1981 to 2016 the Pettitt test indicated the months of March and June with changes in the minimum air temperature, this result also coincided with the months with positive trends.